Assessment and optimization of the fast inertial relaxation engine (FIRE) for energy minimization in atomistic simulations and its implementation in LAMMPS - Guénolé, Julien; Nöhring, Wolfram G.; Vaid, Aviral; Houlle, Frederic; Xie, Zhuocheng; Prakash, Aruna; Bitzek, Erik (Computational Materials Science, 2020)
In atomistic simulations, pseudo-dynamical relaxation schemes often exhibit better performance and accuracy in finding local minima than line-search-based descent algorithms like steepest descent or conjugate gradient. Here, an improved version of the fast inertial relaxation engine (FIRE ) and its implementation within the open-source atomistic simulation code LAMMPS is presented. It is shown that the correct choice of time integration scheme and minimization parameters is crucial for the performance of FIRE.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Atomistic simulation; FIRE; IMD; LAMMPS; Pseudo-dynamics; Relaxation

Microscopic Deformation Modes and Impact of Network Anisotropy on the Mechanical and Electrical Performance of Five-fold Twinned Silver Nanowire Electrodes - Schrenker, Nadine; Xie, Zhuocheng; Schweizer, Peter; Moninger, Marco; Werner, Felix; Karpstein, Nicolas; Mackovic, Mirza; Spyropoulos, Georgios; Göbelt, Manuela; Christiansen, Silke H.; Brabec, Christoph; Bitzek, Erik; et al. (ACS nano, 2020)
Silver nanowire (AgNW) networks show excellent optical, electrical, and mechanical properties, which make them ideal candidates for transparent electrodes in flexible and stretchable devices. Various coating strategies and testing setups have been developed to further improve their stretchability and to evaluate their performance. Still, a comprehensive microscopic understanding of the relationship between mechanical and electrical failure is missing. In this work, the fundamental deformation modes of five-fold twinned AgNWs in anisotropic networks are studied by large-scale SEM straining tests that are directly correlated with corresponding changes in the resistance. A pronounced effect of the network anisotropy on the electrical performance is observed, which manifests itself in a one order of magnitude lower increase in resistance for networks strained perpendicular to the preferred wire orientation. Using a scale-bridging microscopy approach spanning from NW networks to single NWs to atomic-scale defects, we were able to identify three fundamental deformation modes of NWs, which together can explain this behavior: (i) correlated tensile fracture of NWs, (ii) kink formation due to compression of NWs in transverse direction, and (iii) NW bending caused by the interaction of NWs in the strained network. A key observation is the extreme deformability of AgNWs in compression. Considering HRTEM and MD simulations, this behavior can be attributed to specific defect processes in the five-fold twinned NW structure leading to the formation of NW kinks with grain boundaries combined with V-shaped surface reconstructions, both counteracting NW fracture. The detailed insights from this microscopic study can further improve fabrication and design strategies for transparent NW network electrodes.<br
Keywords: silver nanowire; five-fold twinning; transparent electrode; buckling; kinks; transmission electron microscopy; molecular dynamics

Origins of strengthening and failure in twinned Au nanowires: Insights from in−situ experiments and atomistic simulations - Xie, Zhuocheng; Shin, Jungho; Renner, Jakob; Prakash, Aruna; Gianola, Daniel S.; Bitzek, Erik (Acta Materialia, 2020)
The deformation behavior of ⟨110⟩-oriented twinned Au nanowires (NWs) with multiple longitudinal coherent twin boundaries (CTBs) under tension is studied using in−situ experiments and molecular dynamics (MD) simulations. The twinned NWs show higher yield strength than the single-crystalline NWs with similar diameter. Postmortem observations using electron microscopy and MD simulations show that the presence of CTBs transitions the governing mechanism from twinning-mediated deformation in single-crystalline NWs to strongly localized deformation. MD simulations reveal that the intersection of deposited partial dislocations at the CTB with the free surfaces plays an important role in the transmission of the dislocation, leading to the formation of full dislocations instead of partial dislocations and twinning in the case of single-crystalline NWs. The repeated activation of full dislocation slip leading to localized deformation is furthermore dependent on the relative orientation of surface facets to the activated Burgers vectors. The results of this work enhance the understanding of deformation mechanisms of twinned nano-objects and suggest design strategies for mechanical systems at the nanoscale.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Coherent twin boundary; In−situ tension test; Molecular dynamics; Nanowire; Plasticity

Wedge-shaped twins and pseudoelasticity in fcc metallic nanowires under bending - Nöhring, Wolfram Georg; Möller, Johannes; Xie, Zhuocheng; Bitzek, Erik (Extreme Mechanics Letters, 2016)
WW1::1079
Keywords: Simulation and Modeling